2020
DOI: 10.1007/s43032-020-00319-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum VEGF Predicts Abnormally Invasive Placenta Better than NT-proBNP: a Multicenter Case-Control Study

Abstract: The aim of this study was to test if maternal serum vascular endothelial growth factor (VEGF) or N-terminal pro B-type natriuretic peptide (NT-proBNP) predicts abnormally invasive placenta (AIP) better. Secondary objective was to test whether the serum levels of VEGF and NT-proBNP can predict the degree of invasion. In a multicenter case–control study design, gestational age-matched serum samples from pregnant women with AIP (n = 44) and uncomplicated pregnancies (n = 55) who had been enrolled at Charité – Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Nowadays, the researchers try to find biochemical markers of PAS, which may be potential markers for the diagnosis of the severity of PAS. Schwickert A et al (26) found that the level of VEGF in maternal serum could predict the severity of PAS. Shainker SA et al (27) found that the soluble VEGF receptor 2, soluble Tie2, median plasminogen activator inhibitor one concentrations, and median antithrombin III concentrations in maternal plasma were associated with the severity of PAS.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the researchers try to find biochemical markers of PAS, which may be potential markers for the diagnosis of the severity of PAS. Schwickert A et al (26) found that the level of VEGF in maternal serum could predict the severity of PAS. Shainker SA et al (27) found that the soluble VEGF receptor 2, soluble Tie2, median plasminogen activator inhibitor one concentrations, and median antithrombin III concentrations in maternal plasma were associated with the severity of PAS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated significantly higher thirdtrimester maternal serum VEGF levels in PAS cases compared to controls [33][34][35] while others had significantly lower VEGF levels in cases. 30,36 Furthermore Biberoglu et al 25 and Naghshineh and Razaghi 31 showed no significant differences in VEGF levels between both groups. After excluding studies with high risk of bias, 30,31,33,36 results demonstrated significantly higher third-trimester serum VEGF levels among PAS cases when compared to controls (SMD = 3.15, 95% confidence interval [CI] = 0.65-5.66, p = 0.01) (Figure 3b).…”
Section: Third-trimester Serum Levels Of Vegf and Pasmentioning
confidence: 90%
“…28,29 Finally, eight studies were included in this meta-analysis. 25,[30][31][32][33][34][35][36] All of them reported third trimester serum VEGF levels, 25,[30][31][32][33][34][35][36] while seven studies reported third trimester sFlt-1 levels, 25,[31][32][33][34][35][36] and only three studies explored PlGF levels. 25,32,36 The characteristics of the included studies are shown in Table 1.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental tissue can be seen invading through the myometrium and serosa, sometimes even into the urinary bladder, parametria, or even the colon [4][5][6]. In addition to excessive extravillous trophoblastic invasion, abnormal maternal vascular remodeling (i.e., neoangiogenesis) is one of the driving factors of increased placental invasiveness [7][8][9][10]. Angiogenic growth factors, such as vascular endothelial growth factor and angiopoietin-2, are upregulated in PAS lysates.…”
Section: Introductionmentioning
confidence: 99%